Immagini d'Italia e d'Europa nella letteratura e nella documentazione di viaggio nel XVIII e nel XIX secolo Atti del seminario internazionale (Firenze, 1999-2001) - Isenburg, Teresa; Pasta, Renato (Atti, 2004)
The book collects the interventions at the seminar "Images of Italy and Europe in literature and travel documentation in the 18th and 19th centuries", held at the Department of Historical and Geographical Studies of the University of Florence in 1999-2001. It addresses the problem of the creation of borders (political, administrative, linguistic, religious) in Europe and in Brazil from the Middle Ages to the beginning of the 20th century, with particular regard to the period between the 17th and 18th centuries. The theme of the constitution of borders is a classic of the relationship between history and geography and involves the entire range of human sciences, enabling the comparison with international research results.